Abigail Flitton: capstone - Flitton, Abigail, artist (Colorado State University. Libraries, 2021)
The artist's statement: As an illustrator and designer, I strive to use my skills in drawing and storytelling to create compelling and functional work. Hand-drawn type is a common feature within my work. I also explore the ways in which traditional art media can be melded within the digital world, in order to build off of the foundations of vector illustration and inorganic typography. My work is diverse, showcasing my whimsical illustration style when appropriate, yet utilizing essential design elements of typography and hierarchy to function as a communication tool.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design